Misdiagnosis of Epilepsy Attributed to Inadequate History Taking - Levina Tri Ratana; Suryani Gunadharma; Arifin Soenggono (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: There was a noticeable amount of patient with epilepsy who were misdiagnosed at Dr. Hasan Sadikin General Hospital. Misdiagnosis of epileptic seizure will expose patients to inappropriate managements, and subsequently leads to complications. History taking is an important part for the diagnosis of epileptic seizure. This study aimed to see the improvement of diagnosis based on the adequacy and inadequacy of history taking attributed to misdiagnosis of epileptic seizure by the epilepsy consultant at Dr. Hasan Sadikin General Hospital.Methods: This was a descriptive study using medical records of misdiagnosis of epilepsy. It was indicated by different initial (before epilepsy consultant’s confirmation) and final (after epilepsy consultant’s confirmation) seizure diagnosis at Epilepsy Outpatient Clinic at Dr. Hasan Sadikin General Hospital during the period of January 2007−October 2012.Results: There were 61 medical records with different initial and final seizure diagnosis. This study indicated inadequate history taking in 83.6% patients. Misdiagnosis occurred due to incomplete history taking, absence of reliable witnesses, and misinterpretation of history taking result. History taking by epilepsy consultant improved the misdiagnosis in 27.9% patients. While it is used simultaneously with Electroencephalography (EEG), the result increased to 72.2%.Conclusions: The adequate history taking improved the accuracy of epileptic seizure diagnosis. The simultaneous used of history taking and EEG increased the result. [AMJ.2016;3(2):304–9]DOI: 10.15850/amj.v3n2.775